Major differences between trifluorophosphine and carbonyl ligands in binuclear cyclopentadienyliron complexes. (6th March 2015) - Gong, Shida; Luo, Qiong; Li, Qian-shu; Xie, Yaoming; Bruce King, R.; Schaefer III, Henry F.
Abstract : No low-energy Cp2 Fe2 (PF3 ) n structures have bridging PF3 ligands. Bridging μ-PF2 groups are found combined with terminal F or PF4 ligands. Abstract : The cyclopentadienyliron trifluorophosphine hydride CpFe(PF3 )2 H, in contrast to CpFe(CO)2 H, is a stable compound that can be synthesized by reacting Fe(PF3 )5 with cyclopentadiene. Theoretical studies on the binuclear Cp2 Fe2 (PF3 ) n ( n = 5, 4, 3, 2) derivatives derived from CpFe(PF3 )2 H indicate the absence of viable structures having PF3 ligands bridging Fe–Fe bonds solely through the phosphorus atom. This contrasts with the analogous Cp2 Fe2 (CO) n systems for which the lowest energy structures have two (for n = 4 and 2) or three (for n = 3) CO groups bridging an iron–iron bond. Higher energy singlet Cp2 Fe2 (PF3 )3 structures have a novel four-electron donor bridging η 2 -μ-PF3 ligand bonded to one iron atom through its phosphorus atom and to the other iron atom through a fluorine atom. Other higher energy triplet and singlet Cp2 Fe2 (PF3 )2 structures are of the Cp2 Fe2 F2 (μ-PF2 )2 type having terminal fluorine atoms and bridging μ-PF2 ligands. The lowest energy Cp2 Fe2 (PF3 )5 structure is actually Cp2 Fe2 (PF3 )3 (PF4 )(μ-PF2 ) with a bridging PF2 group and a terminal PF4 group. Such structures are derived from a Cp2 Fe2 (PF3 )4 (μ-PF3 ) precursor by migration of a fluorine atom from the bridging PF3 group to a terminal PF3 group with a low activation energy barrier.